Population pharmacokinetics of clonazepam in saliva and plasma: Steps towards noninvasive pharmacokinetic studies in vulnerable populations. Issue 5 (9th December 2021) - Kruizinga, Matthijs D.; Zuiker, Rob G. J. A.; Bergmann, Kirsten R.; Egas, Annelies C.; Cohen, Adam F.; Santen, Gijs W. E.; van Esdonk, Michiel J.
Abstract : Aim: Traditional studies focusing on the relationship between pharmacokinetics (PK) and pharmacodynamics necessitate blood draws, which are too invasive for children or other vulnerable populations. A potential solution is to use noninvasive sampling matrices, such as saliva. The aim of this study was to develop a population PK model describing the relationship between plasma and saliva clonazepam kinetics and assess whether the model can be used to determine trough plasma concentrations based on saliva samples. Methods: Twenty healthy subjects, aged 18‐30, were recruited and administered 0.5 or 1 mg of clonazepam solution. Paired plasma and saliva samples were obtained until 48 hours post‐dose. A population pharmacokinetic model was developed describing the PK of clonazepam in plasma and the relationship between plasma and saliva concentrations. Bayesian maximum a posteriori optimization was applied to estimate the predictive accuracy of the model. Results: A two‐compartment distribution model best characterized clonazepam plasma kinetics with a mixture component on the absorption rate constants. Oral administration of the clonazepam solution caused contamination of the saliva compartment during the first 4 hours post‐dose, after which the concentrations were driven by the plasma concentrations. Simulations demonstrated that the lower and upper limits of agreements between true and predicted plasma concentrations were −28% to 36% with one saliva sample. Increasing the number of saliva samples improved these limits to −18% to 17%. Conclusion: The developed model described the salivary and plasma kinetics of clonazepam, and could predict steady‐state trough plasma concentrations based on saliva concentrations with acceptable accuracy.